2020
DOI: 10.3390/biom10020200
|View full text |Cite
|
Sign up to set email alerts
|

Double-Stranded RNAs (dsRNAs) as a Sustainable Tool against Gray Mold (Botrytis cinerea) in Grapevine: Effectiveness of Different Application Methods in an Open-Air Environment

Abstract: Grapevine is one of the most important and globally widespread fruit species, with a high impact on the economy of many countries but with an intense environmental effect. Therefore, new environmentally friendly defense strategies against fungal pathogens are needed for more sustainable agriculture. A novel emerging approach is spray-induced gene silencing (SIGS), which concerns the exogenous application of double-stranded RNA (dsRNA) inducing enhanced plant resistance against fungal pathogens. Here, we tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(80 citation statements)
references
References 65 publications
2
78
0
Order By: Relevance
“…Furthermore, the functionality of absorbed exogenous RNAi molecules offers excellent adaptability and flexibility in securing the required effects on gene expression of fungi, even without the need to genetically modify the targeted pathogen [ 11 , 32 ]. This homology-based gene silencing stimulated by transgenes (co-suppression), antisense, or dsRNAs has been demonstrated in several plant pathogenic fungi/oomycetes, including different mold fungi, such as Botrytis cinerea , Neurospora crassa , and Sclerotinia sclerotiorum [ 11 , 18 , 33 , 34 ]; blast, blight, and rust fungi, such as Fusarium asiaticum , Fusarium graminearum , Magnaporthe oryzae, and Puccinia striiformis f. sp. tritici [ 17 , 35 , 36 , 37 , 38 ]; mildew, and others, such as Blumeria graminis , Cochliobolus sativus, and Venturia inaequalis [ 39 , 40 , 41 ].…”
Section: Rnai For Resistance Against Plant Pathogenic Fungimentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the functionality of absorbed exogenous RNAi molecules offers excellent adaptability and flexibility in securing the required effects on gene expression of fungi, even without the need to genetically modify the targeted pathogen [ 11 , 32 ]. This homology-based gene silencing stimulated by transgenes (co-suppression), antisense, or dsRNAs has been demonstrated in several plant pathogenic fungi/oomycetes, including different mold fungi, such as Botrytis cinerea , Neurospora crassa , and Sclerotinia sclerotiorum [ 11 , 18 , 33 , 34 ]; blast, blight, and rust fungi, such as Fusarium asiaticum , Fusarium graminearum , Magnaporthe oryzae, and Puccinia striiformis f. sp. tritici [ 17 , 35 , 36 , 37 , 38 ]; mildew, and others, such as Blumeria graminis , Cochliobolus sativus, and Venturia inaequalis [ 39 , 40 , 41 ].…”
Section: Rnai For Resistance Against Plant Pathogenic Fungimentioning
confidence: 99%
“…The E. coli HT115 (DE3) harbors the pro-phage λDE3 encoding the Isopropyl β-D-1-thiogalactopyranoside (IPTG) inducible T7 polymerase gene for dsRNA transcription [ 101 , 113 , 115 , 116 ]. Even though, the bacterial production systems may contain bacterial homologous DNA molecules; that may affect the RNA quality and applicability, crude extracts of dsRNA can be applied on plants to test its efficiency against plant pathogens and pests [ 18 , 117 ]. Researchers demonstrated that bacterially expressed dsRNAs can be used to induce RNAi in fungus [ 18 ], virus [ 49 ], worms [ 118 ], and in insect pests [ 56 , 119 ].…”
Section: Small Rna Production Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Selecting fungicide sites of action, Nerva and colleagues constructed a single long dsRNA molecule that exerted protection against grey mold in vitro on grapevine detached leaves and grapes at post-harvest, applied through the high-pressure spray and petiole adsorption. Despite different levels of protection being recorded among the dsRNAs delivery methods, interestingly, all the techniques that facilitate the provision of intact dsRNA to the fungus were assumed as effective [ 128 ].…”
Section: Rnai: Host- or Spray-induced Gene Silencing Against Fungimentioning
confidence: 99%
“…Unsurprisingly, plant researchers have lately resorted to induction of RNAi by exogenous application of RNA molecules having the potential to trigger RNAi (exogenous RNAi, exo-RNAi), as an effective and transgene-free alternative to GM crops [31][32][33][34][35]. Indeed, dsRNAs/siRNAs were applied in plants by methods such as spraying, petiole uptake, trunk injection and root absorption in order to modify plant gene expression [36][37][38][39] and to confer resistance against viruses [40][41][42][43][44], fungi [45][46][47][48][49] and insects [50][51][52][53][54]. In the near future, one may envisage that exo-RNAi could potentially replace conventional herbicides, fungicides and insecticides, and a great amount of effort is invested in this direction by most major crop industries [55].…”
mentioning
confidence: 99%